In vivo and in vitro screening for resistance against Penicillium allii in garlic accessions - Salinas Palmieri, Maria Cecilia; Cavagnaro, Pablo (Springer, 2019)
Garlic blue mold disease, caused by Penicillium allii, is responsible for important economic losses produced yearly in garlic field crops and in postharvest storage. The identification of genetic resistance sources may help in the management of this disease. The present study investigated in vivo and in vitro antifungal effects of a genetically-diverse garlic collection against P. allii in two growing seasons. Cloves of garlic accessions were inoculated with P. allii conidia, and lesion area and sporulation of the fungus in the clove were estimated as a means to characterize the accessions response to the infection. Significant and continuous variation was found among the accessions (p < 0.001), suggesting a quantitative mode of resistance against P. allii in this garlic collection. ‘Castaño’ and ‘Peteco’ were consistently the most resistant and susceptible genotypes, respectively. Culture media of the fungus supplemented with crude garlic extracts (CGEs) revealed significant inhibition of P. allii growth in vitro by all the garlic accessions, with fungal-growth inhibition being dose-dependent up to a concentration of 20–26% (v/v), beyond which the CGEs became fungicidal. These data indicate that garlic bulbs have antifungal compounds, which at high concentration can be fungicidal for P. allii. CGEs of ‘Castaño’ and a few other accessions were consistently the more inhibitory extracts. Total phenolics and pyruvate (an estimator of the total thiosulfinates content) concentration in the garlic bulbs was not associated with P. allii resistance in vivo, but their content in the CGEs correlated significantly and negatively with the fungal growth in vitro (r = −0.38 to −0.72), suggesting that these compounds have antifungal effect, but their content is not the main factor conditioning P. allii resistance in vivo.